Nanopartículas multifuncionais para hipertermia, termometria e imagem de fluorescência nas janelas biológicas - Ximendes, Erving Clayton (2018)
In this thesis, the use of core/shell engineering for the synthesis of fluorescent nanoparticles (NPs) capable of operating as nanothermometers, nanoheaters and/or contrast agents for fluorescence imaging in small animal models is explored. The materials here studied – rare-earth (Nd3+, Yb3+, Tm3+ and/or Er3+) doped NPs and PbS/CdS/ZnS quantum dots (QDs) – presented emission and/or excitation bands in the so-called biological windows, where light penetration into tissues is maximal, allowing for ex vivo and in vivo applications. It was demonstrated that the spatial separation between the rare-earth ions, achieved by the core/shell nano-engineering, resulted not only in a considerable improvement on the values of thermo-optical parameters such as the light-heat conversion efficiency and the relative thermal sensitivity but also on a multi-functionality of the nanosystems. As a consequence, innovative applications in nanothermometry were successfully accomplished when developing this thesis. Among those applications, one can mention the study in real time of the thermal dynamics of an in vivo tissue, the detection and monitoring of cardiovascular diseases and the recording of in vivo thermal images and videos at a subcutaneous level by means of a ratiometric approach. The results here presented open up avenues for new diagnosis and control techniques that can revolutionize the current methods found in biomedicine.